FEATURES OF RESULT BASED FINANCING HIGHER EDUCATION - Iryna Kalenyuk; Olena Grishnova; Liudmyla Tsymbal; Deniss Djakons (Scientific Journal of Pedagogy and Economics, 2021)
The key role of the education system in the formation of a knowledge society is raising the issue of improving its financing. In the face of new challenges and aggravation of global competition, the mechanism for financing the higher education system is being transformed. The need to increase funding is manifested in expanding financial sources and improving the management of various financial flows. Increasing the effectiveness of public funding is becoming an important issue, which remains the main source of financial revenues for institutions of higher education in countries of the world. A promising practice in the world is the use of funding based on the results of activity, which is becoming more widespread in various areas of economic activity. The purpose of this article is to study the current world-wide practice of applying results-based financing of higher education and defining promising directions for its implementation in Ukraine. The essence and features of RBF - Result Based Financing (RBF) method, including in the system of higher education, are revealed. The existing approaches to financing higher education institutions in the world based on results are systematized, the main criteria for their definition are identified: on the basis of inputs, process, output, output. The world practice of using higher education institutions financing based on the results, positive and negative consequences of its implementation is highlighted and summarized. The necessity of using RBF funding in the system of native education is proved, the main directions and areas of its use are determined. The application of a two-tier model of financing higher education institutions in Ukraine is proposed, which combines the traditional cost-oriented approach and funding based on the results of the activity.